2015
DOI: 10.1016/j.ijcard.2015.03.344
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and fetal outcomes of pregnancy with Fontan circulation: A multicentric observational study

Abstract: a b s t r a c t Keywords: Pregnancy Fontan circulation Congenital heart disease AnticoagulationBackground: Despite serious long-term sequel, women with Fontan palliation have reached childbearing age. However there is paucity of data on the pregnancy outcomes and management of this condition. We aimed to determine the maternal and fetal outcomes of pregnancy in women with Fontan palliation. Methods: This multicentric, retrospective study included women with Fontan circulation followed in 13 French specialized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 26 publications
7
99
2
1
Order By: Relevance
“…In contrast to published series, we observed a high rate of pre-term delivery (92%) and a higher rate of CS delivery [7,8,10]. The latter may be attributed to a higher rate of maternal and fetal morbidity seen in our cohort necessitating delivery rather than allowing spontaneous labour to take place.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to published series, we observed a high rate of pre-term delivery (92%) and a higher rate of CS delivery [7,8,10]. The latter may be attributed to a higher rate of maternal and fetal morbidity seen in our cohort necessitating delivery rather than allowing spontaneous labour to take place.…”
Section: Discussioncontrasting
confidence: 99%
“…Maternal cardiovascular morbidity, primarily due to atrial arrhythmias and deterioration of functional status has been observed. The rate of spontaneous miscarriages varied (27-65%) may have been underestimated in some of the series [6,10]. Moreover, a significant proportion of pregnancies (69-81%) resulted in premature births in the contemporary series [7,8,10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…80,81 Not surprisingly, among adult women with CHD who become pregnant, adverse cardiovascular events occurring in pregnancy and childbirth are considerably more likely during admission for delivery than the general population, particularly among those with complex CHD or pulmonary hypertension. [82][83][84][85] As a result of these pathophysiologies, significant, lesion-specific effects on life expectancy can be forecast (Figure 7).…”
Section: Adults With Chdmentioning
confidence: 99%